Love Quotient: Spirit Tasawuf dalam Syari'ah Marketing - Iwan Fahri Cahyadi (Esoterik: Jurnal Akhlak dan Tasawuf, 2019)
Jack Ma is a founder and is the highest executive officer of the Alibaba Group. Alibaba Group Company is a company engaged in the field of e-Commerce. Jack Ma gave the opinion that a leader who wants to succeed not only has a high Intelligence Quotient (IQ) and Emotional Quotient (EQ), but also a Love Quotient (LQ). Meanwhile psychologists have discovered human intelligence, namely IQ, EQ and Spiritual Quotient (SQ). Islam itself says that Fitrah is the highest form of intelligence. Differences of opinion need to be studied more deeply, both in terms of business, psychology, and religion. This article uses qualitative methods. The findings of this study confirm that the term Love Quotient in a business perspective, Spiritual Quotient (SQ) in psychology and Fitrah in Islam is a concept that has the same nature even though it uses different terms. The conclusion of this study is that between religion and science support each other and sharia marketing can be applied if LQ, SQ and Islam Fitrah are attached to a marketer.